Application of the DAWN clinical imaging mismatch and DEFUSE 3 selection criteria: benefit seems similar but restrictive volume cut‐offs might omit potential responders. (10th May 2018) - Ducroux, C.; Khoury, N.; Lecler, A.; Blanc, R.; Chetrit, A.; Redjem, H.; Ciccio, G.; Smajda, S.; Escalard, S.; Desilles, J.‐P.; Mazighi, M.; Ben Maacha, M.; et al.
Abstract : Background and purpose: An external validation of the selection criteria of diffusion‐weighted imaging or computerized tomography perfusion assessment with clinical mismatch in the triage of wake‐up and late‐presenting strokes undergoing the Neurointervention with Trevo (DAWN) and the Endovascular Therapy Following Imaging Evaluation for Ischemic Stroke (DEFUSE3) trials was conducted in a cohort of unknown onset stroke (UOS) patients treated with thrombectomy. Methods: A validation cohort of UOS patients was selected from a prospectively collected thrombectomy database to match the inclusion criteria of DAWN and DEFUSE 3. Patients with an initial National Institutes of Health Stroke Scale (NIHSS) ≥10 were stratified according to the DAWN selection criteria. Patients ≤90 years old with an initial NIHSS ≥6 were stratified according to the DEFUSE 3 selection criteria. The proportions of patients with a modified Rankin Scale (mRS) ≤2 at 3 months follow‐up were compared between DAWN‐eligible patients and the DAWN trial thrombectomy group, and between DEFUSE 3‐eligible patients and the DEFUSE 3 trial thrombectomy group. Results: Of the 60/102 (59%) DAWN‐eligible patients, 26 patients (43%) reached a mRS ≤2 at 3 months follow‐up [versus 52/107 patients (49%) in the DAWN trial thrombectomy group; P = 0.52]. Of the 100/117 (85%) DEFUSE 3‐eligible patients, 48 patients (48%) reached a mRS ≤2 at 3 months follow‐up [versus 41/92 patients (45%) in the DEFUSE 3 trial thrombectomy group; P = 0.67]. Of the DAWN‐ineligible and DEFUSE 3‐ineligible patients who underwent thrombectomy, 38% (16/42) and 41% (7/17) of patients reached a mRS ≤2, respectively. Conclusion: The results of the DAWN and DEFUSE 3 trials were externally validated in a UOS cohort where the trials' selection criteria identified a similar proportion of responders to thrombectomy.